On FSUM model and applications - Chung, Dang Huu (Vietnam Journal of Mechanics, 2008)
In this paper a 3D model (FSUM) on tidal flows with sediment transport and bed morphology process taking into account the temperature-salinity exchange in estuaries and coastal zones is introduced in more detail. The implicit finite difference method based on semi-Lagrange splitting is used. The software is coded with FORTRAN 90/95. The open boundary condition kinds together source/sink terms are well treated so that it can be applied to every computing domain with the complicated geometry. The software is validated and applied for many different cases and shows the ability of application in practice